Silicosis presenting as bilateral hilar lymphadenopathy. Issue 11 (November 1996) - Baldwin, D R; Lambert, L; Pantin, C F; Prowse, K; Cole, R B
Abstract : Classical radiographic features of patients presenting with silicosis are diffuse interstitial shadowing with subsequent enlargement of hilar nodes, sometimes with "eggshell" calcification. Five case histories are described of workers who were exposed to silica and presented initially with bilateral hilar lymphadenopathy without radiographic evidence of interstitial lung disease. One case progressed to show features of silicosis.